MiR‐29 coordinates age‐dependent plasticity brakes in the adult visual cortex. (18th December 2020) - Napoli, Debora; Lupori, Leonardo; Mazziotti, Raffaele; Sagona, Giulia; Bagnoli, Sara; Samad, Muntaha; Sacramento, Erika K; Kirkpartick, Joanna; Putignano, Elena; Chen, Siwei; Terzibasi Tozzini, Eva; Tognini, Paola; et al.
Abstract :